Identifying Non-Value Adding Activities to Enhance Productivity in Freight Terminals A Case Study of DB Schenker’s Terminal Operations - Andersson, Ida; Johnsen, Filippa (My University, 2023)
In today’s society, with rising inflation and an increasingly globalized market, companies and organizations are facing ever greater challenges. One company facing these challenges is DB Schenker, a logistics provider offering terminal operations. To remain competitive in today’s market, DB Schenker’s Terminal Department is working on measuring non-value adding activities (referred to as support activities) through its process-oriented time registration in a system called Check In Check Out. The purpose of Check in Check out is to carry out a detailed productivity measurement and gain insight into the amount of time spent on each process in the terminal. Hence, this thesis aims to provide the company with a better insight into its non-value adding activities and to identify potential areas of improvements in order to increase the overall productivity. During the thesis work, observations of terminal operations and interviews with terminal employees have taken place. Together with the literature review conducted, the research questions were answered. Conclusions of the study revealed that activities related to the paper waybill and support of drivers should continue to be registered under their current subprocess. While activities related to leadership, meetings and add-on services should no longer be classified as support activities, since these activities are considered value adding. Furthermore, the study also found that there are three main reasons why terminals spend a significant amount of time on non-value adding support activities. Firstly, many of the support activities are related to the handling of the paper waybill. In addition, a nondynamic way of working and too general central guidelines regarding the registration in Check in Check Out were identified. DB Schenker is recommended to develop and make greater use of existing digital tools, develop the procedures of following up deviations in the coding of waybills, enlarge the font of the sorting codes and eventually completely digitize the information flow. In addition, DB Schenker should utilize a more flexible workforce, facilitate the punching process by adding more punching clocks and educate the terminal employees about the purpose of Check In Check Out. Finally, DB Schenker is recommended to develop clearer central guidelines for how terminal workers should register their activities in Check In Check Out to increase the accuracy of the productivity measurements.
Keywords: terminal operations; value adding activities; non-value adding activities; productivity measurements; paper waybill; digital transformation